A Proposal to Define and Classify the Logistics Strategies of Maritime Container Terminal Operators - Robert MAREK (Communications of International Proceedings, 2022)
In today’s highly competitive environment, many companies, include container operators create logistics strategies which shall improve them market position. Unfortunately, there is not clearly describe logistic strategies on literature as general. Container terminal operators has to ensure the smooth flow of container units and cargo as well as information throughout the company’s logistics pipeline. To compete effectively, terminal operators must recognize the strategic importance of the logistics function. Moreover, terminal operators permanently face market changes, the increased demand of marine transports, the demand for new, bigger and more specialized vessels, has increased the competition among container terminals. The selection of a suitable logistic strategy is important for container terminal operators wishing to improve their financial results. Logistic strategies also add value to the operators that uses suitable logistic strategies to satisfy its customers. Conclusion: Operators of container terminals, operating on a global scale, increasingly focus their attention on the implementation and execution of logistics strategies. Depending on the adopted logistics strategy, the level and scope of services offered varies - from simple handling and storage activities to activities related to flow management in the global supply network - acting as an integrator of the flow of containerized cargo. Moreover, the article attempts to identify the possibilities of adapting logistics strategies implemented by maritime operators of container terminals.
Keywords: logistics strategies; marine container terminal operators